Restorative Effects of Inulin From Codonopsis pilosula on Intestinal Mucosal Immunity, Anti-Inflammatory Activity and Gut Microbiota of Immunosuppressed Mice - Zou, Yuan-Feng; Li, Cen-Yu; Fu, Yu-Ping; Feng, Xin; Peng, Xi; Feng, Bin; Li, Li-Xia; Jia, Ren-Yong; Huang, Chao; Song, Xu; Lv, Cheng; Ye, Gang; et al. (Frontiers in Pharmacology, 2022)
An inulin (CPPF), isolated from a traditional Chinese herbal medicine Codonopsis pilosula, was characterized and demonstrated with potential prebiotic activity in vitro before. Based on its non-digested feature, the intestinal mucosa and microbiota modulatory effects in vivo on immunosuppressed mice were investigated after oral administration of 200, 100 and 50 mg/kg of CPPF for 7 days. It was demonstrated that the secretions of sIgA and mucin 2 (Muc2) in ileum were improved by CPPF, as well as the anti-inflammatory activities in different intestine parts. The intestine before colon could be the target active position of CPPF. As a potential prebiotic substance, a gut microbiota restorative effect of CPPF was also presented by mainly modulating the relative abundance of Eubacteriales, including Oscillibacter, unidentified Ruminococcus and Lachnospiraceae after high-throughput pyrosequencing of V4 region of 16S rRNA analysis. All these results indicated that this main bioactive ingredient inulin from C. pilosula was a medicinal prebiotic with mucosal immune-enhancement, anti-inflammatory and microbiota modulation functions.